1999
DOI: 10.1029/1999jb900251
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Costa Rica convergent margin, offshore Nicoya Peninsula

Abstract: Abstract. We present the results of a seismic refraction survey conducted offshore Costa Rica near the Nicoya Peninsula. A dip profile and three strike profiles were carried out over 22 ocean bottom hydrophones and seismographs and were also recorded by land receivers. These data are used to construct a crustal structure model of the convergent margin from 20 km seaward of the Middle America Trench onto the Nicoya Peninsula. The best constrained portion of our model is the velocity at the top of the margin wed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 52 publications
7
108
1
2
Order By: Relevance
“…The slope of the seafloor on the wedge is 5.4°. The subducting plate dips 6°for the first 30 km of the subduction zone, after which the dip angle increases to 13° [ Christeson et al, 1999].…”
Section: Methodsmentioning
confidence: 99%
“…The slope of the seafloor on the wedge is 5.4°. The subducting plate dips 6°for the first 30 km of the subduction zone, after which the dip angle increases to 13° [ Christeson et al, 1999].…”
Section: Methodsmentioning
confidence: 99%
“…Seismic velocities of 4-6 km/s beneath the lower and middle slope of the Nicoya Peninsula forearc are interpreted as igneous rock, presumably the ophiolitic Nicoya Complex (Chrsteson et al, 1999;Sallares et al, 2001). Therefore, Ranero and von Huene (2000) concluded that the eroded material transported into the subduction zone is igneous basement from the forearc.…”
Section: Underplating Vs Tectonic Erosionmentioning
confidence: 99%
“…The throws on these extensional faults are equal to or greater than the thickness of the sediment column (--400 m) . Offshore of Costa Rica, normal faulting in the subducting plate is not as pronounced (Shipley and Moore, 1986;Hinz et al, 1996;Ye et al, 1996;, Chrsteson et al, 1999. It was therefore thought possible that beneath Nicaragua, large basement faults facilitated efficient subduction of the shallow, lOBe-bearing sediment layer to the arc volcanic roots, whereas this absence of fault relief offshore of Costa Rica could lead to removal of the uppermost sediment layer through underplating (Kelly and Driscoll, 1998).…”
Section: Background and Motivationmentioning
confidence: 99%
“…The Caribbean overriding plate, for example, shows a dramatic thinning from 16 km at the coastline in Guatemala [Ye et al, 1996], far and not influenced by Cocos Ridge subduction , to 12-14 km in Nicoya [Christeson et al, 1999;Sallares et al, 2001], where the sharp increase in subduction erosion rate is in agreement with the beginning of thickened crust subduction , to 3 km in Osa Peninsula [Walther, 2003]. A general increase in erosional rates along the margin toward Cocos Ridge can also be inferred from the trench morphology, where a sudden landward shift of the trench axis strike occurs coincident with the area of Figure 13.…”
Section: Postsubduction Deformation: Osa Mélange Exhumationmentioning
confidence: 99%